2017
DOI: 10.1177/0265659017735392
|View full text |Cite
|
Sign up to set email alerts
|

Combining implicit and explicit intervention approaches to target grammar in young children with Developmental Language Disorder

Abstract: Children with developmental language disorder are likely to experience difficulties with morphosyntax, especially regular past tense marking. Few studies have evaluated the effectiveness of intervention to improve morphosyntax in young school-aged children with DLD. This study investigated the efficacy of combined explicit and implicit intervention techniques delivered by a speech pathologist to improve receptive and expressive grammar, including the use of past tense morphosyntax, using a multiple baseline si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…There were no differences between groups on production or grammaticality judgment of 3S marking (the extension measure), suggesting no effect of the intervention on these measures. Similar to findings from Calder et al (2018Calder et al ( , 2020, the limited improvement on 3S, suggests that even linguistically similar structures are unlikely to improve without direct intervention. This finding is consistent with existing studies (e.g., Eidsvåg et al, 2019) suggesting grammar intervention must be targeted to specific targets to yield improvement in children with DLD.…”
Section: Research Question 3: Does Third Person Singular Marking But Not Possessive 'S Marking Improve Following Intervention For -Ed Comsupporting
confidence: 58%
See 2 more Smart Citations
“…There were no differences between groups on production or grammaticality judgment of 3S marking (the extension measure), suggesting no effect of the intervention on these measures. Similar to findings from Calder et al (2018Calder et al ( , 2020, the limited improvement on 3S, suggests that even linguistically similar structures are unlikely to improve without direct intervention. This finding is consistent with existing studies (e.g., Eidsvåg et al, 2019) suggesting grammar intervention must be targeted to specific targets to yield improvement in children with DLD.…”
Section: Research Question 3: Does Third Person Singular Marking But Not Possessive 'S Marking Improve Following Intervention For -Ed Comsupporting
confidence: 58%
“…Inconsistent with previous findings (Calder et al, 2018(Calder et al, , 2020, mean scores on standardized assessments did not significantly improve following intervention. The current study differs in a critical aspect: the addition of a waiting control group.…”
Section: Research Question 2: Do Standardized Measures Of Grammar Improve Followingsupporting
confidence: 52%
See 1 more Smart Citation
“…The pedagogical support specialist for young children and their families should have the following skills (BRUINSMA, WIJNEN, GERRITS, 2020;CALDER, CLAESSEN, LEITÃO, 2018):…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that 3 investigations (in which the therapies were not focused on grammatical comprehension) showed that children also benefited at a comprehensive level. Thus, the work of Calder et al 42 , which uses combined approaches, Zwitserlood et al 40 , which uses the metalinguistic approach and Camarata et al 26 that uses implicit approaches to work expressive grammar, indicated that children were favored both expressively and comprehensively. These results suggest that the approach to grammatical comprehension can be performed indirectly, in particular the explicit or metalinguistic approach seems to be useful for receptive grammatical difficulties.…”
Section: Englishmentioning
confidence: 99%